The Role of Serotonin beyond the Central Nervous System during Embryogenesis - Lv, Junhua; Liu, Feng (Frontiers in Cellular Neuroscience, 2017)
Serotonin, or 5-hydroxytryptamine (5-HT), is a well-known neurotransmitter that plays vital roles in neural activities and social behaviors. Clinically, deficiency of serotonin is linked with many psychiatric disorders. Interestingly, a large proportion of serotonin is also produced outside the central nervous system (CNS). There is increasing evidence demonstrating important roles of serotonin in the peripheral tissues. Here, we will describe the multiple biological functions of serotonin in hematopoietic system, such as development of hematopoietic stem and progenitor cells (HSPCs), differentiation of hematopoietic cells, maintenance of vascular system, and relationship with hematological diseases. The roles of serotonin in inflammatory responses mediated by hematopoietic cells as well as in liver regeneration are also discussed. Our recent understandings of the impact of serotonin on hematopoietic system, immune responses, and tissue regeneration support utilization of serotonin as a potential therapeutic target for the treatment of hematological diseases and organ repair in clinic.